The Architecture of Loneliness: A Systematic Literature Review of Elderly Housing Design - Aziza Rindra Luna Satriono; Joko Adianto (Department of Architecture Universitas Muhammadiyah Jakarta, 2025)
The challenges posed by an aging population are profound, particularly in ensuring that the living environments of older adults foster their overall well-being. This study undertakes a systematic literature review (SLR) of 39 academic sources published between 2005 and 2024, critically analyzing the extent to which housing design and facilities alleviate loneliness among the elderly. The evidence reveals that while considerations of accessibility and physical safety remain essential, truly supportive housing must also cultivate opportunities for social engagement, personal autonomy, and emotional connection. Architectural elements such as communal areas, spatial configuration, and the presence of social infrastructure emerge as pivotal in diminishing the experience of loneliness. Although national policy instruments—such as Presidential Regulation No. 88 of 2021 and Minister of Social Affairs Regulation No. 4 of 2017—articulate a strategic vision for age-friendly housing in Indonesia, their execution remains constrained, particularly in terms of contextualizing design principles within local sociocultural realities. This study underscores the imperative of adopting a holistic and integrated framework that interweaves architectural planning, community-based initiatives, and participatory governance to cultivate inclusive and resilient environments for older adults. It calls for further inquiry into localized practices and co-creative design processes that meaningfully center the voices and lived experiences of the elderly in shaping both housing solutions and public policy.